The Factors Related with Nursing Spiritual Care Competence - Supriyadi Supriyadi; Gani Apriningtyas Budiyati; Umi Kulsum; Jihan Tirta Yanti; Riskiyanti Riskiyanti (Indonesian Journal of Global Health Research, 2021)
Humans are composed of various dimensions, namely physiological, psychological, sociocultural and spiritual. When sick, all these dimensions are affected. Therefore, nurses must be able to provide holistic nursing care. Holistic nursing care views the spiritual part of the service that must be fulfilled because meeting spiritual needs has the impact of accelerating the patient's healing process. Spiritual nursing care can be implemented if the nurse has spiritual care competence. Spiritual upbringing is influenced by various things including beliefs and values, skills, experience, personality characteristics, motivation, emotional issues, intellectual abilities and organizational culture. The purpose of the study was to determine the factors related to the competence of nurses' spiritual care. The research design used was descriptive correlation with cross sectional approach. The population in this study were clinical nurses in Bantul, Yogyakarta. The sampling technique used was purposive sampling, obtained a sample of 71 respondents. Data collected with spiritual care knowledge and motivation questionnaire, Daily Spiritual Experience Scale (DSES), spiritual care competen scale (SCCS) and than analyzed by Kendall’s Tau. The results of the study were that the majority of nurses had knowledge of high spiritual care 60 respondents (82%), high spirituality 43 respondents (59%), moderate motivation 39 respondents (54%) and moderate spiritual care competence 48 respondents (6%). The variable most related to spiritual care competence is the spirituality of nurses with a p-value of 0.000.